FACTORS INFLUENCING ADOPTION OF A HALAL APP IN A SMALL ISLAND DEVELOPING STATE (SIDS). A CONCEPTUAL FRAMEWORK (International Journal of Islamic Business, 2022)
The fourth technological revolution is here, tailgated by stratospheric advances in emerging technologies meant to improve the daily lives of individuals which come with various functionalities, uses and varieties. We are talking of smartphone applications or Apps and they are a rage nowadays given the unrivaled degree of informativeness, convenience, connectivity and networking opportunities they offer, and have been developed to address the needs of consumers in various sectors namely, banking, shopping, travel, fitness and health, food delivery, mapping, news and education, just to name a few. At the same time, the growing demand for Halal consumption fueled by the boom in the global Halal industry and ethical consumerism, consumers are in dire need of a one-stop medium where information about Halal products is available within reach so as to safely maintain their religious commitments and dieting requirements. Therefore, given the uniqueness of Halal-based Apps and more so the peculiar requirements of Halal consumers, it has become imperative to have studies which investigate the factors which influence Muslims to adopt Halal-based Apps, and the literature clearly lacks in terms of such assessments. Hence, the present research is one of the very first to come up with a conceptual framework which can be used to study the predominant factors which would motivate users to adopt Halal-based App. This research has taken the case of a Halal-based App, named HalaalMoris in a Small Island Developing State (SIDS) like Mauritius.